Analysis of the Physical Education Learning Process Through Online Media - Yudi Nuryadi Somantri (Multidisciplinary Journal of Tourism, Hospitality, Sport and Physical Education, 2024)
Purpose of the study: This study aims to determine the learning process through online media in physical education learning in class VIII. Methodology: This research is a descriptive qualitative research. The sampling technique used is total sampling with the research subjects of class VIII totaling 25. The data collection techniques used were questionnaires and documentation. Main Findings: Based on the results of the research on Physical Education Learning Processes Through Online Media at MTsN 1 Bengkulu City, they have implemented the physical education learning process through online media, it can be seen from the percentage results with an average of 69%. Novelty/Originality of this study: By utilizing online media, learning becomes more flexible and can be accessed from anywhere, changing the traditional paradigm to more inclusive and affordable learning. The results of this research provide new insights into the effectiveness of online media in supporting the teaching and learning process, opening up opportunities for the development of learning methods that are more interactive and responsive to student needs in the future.